Retrospective analysis of COX-2 inhibitors on SIRS in acute pancreatitis - YANG Haibo; FU Xifeng; TIAN Yanzhang; GAO Fei; ZHANG Binbin; MO Shaojian (Zhongguo linchuang yanjiu, 2023)
Objective To investigate the effect of cyclooxygenase-2 (COX-2) inhibitor parecoxib on systemic inflammatory response syndrome (SIRS) in patients with acute pancreatitis (AP). Methods A retrospective analysis was performed on 206 AP patients who were treated in Shanxi Norman Bethune Hospital from April 2021 to April 2022. The patients treated with COX-2 inhibitors were assigned to group A (n=100), and the patients treated with other analgesics were assigned to group B (n=106). The patients with SIRS at admission in group A and B were divided into A1 group (n=48) and B1 group (n=49), and those without SIRS were divided into A2 group (n=52) and B2 group (n=57). The incidence of SIRS in each group was compared, including SIRS duration and rating. The organ failure score (Sequential Organ Failure Assessment, SOFA) and serum CRP level on the 4th day of hospitalization, as well as the length of hospitalization, cost, and incidence of complications between group A and group B were compared. Multivariate logistic regression analysis of risk factors for SIRS in patients who did not experience SIRS at admission. Results Compared with those in group B1, the proportion of patients with SIRS duration< 3 days in group A1 increased, and the proportion of patients with SIRS duration≥ 3 days decreased in group A1（P＜0.05＝. On the 4th day, SIRS score in group A1 was statistically lower than that in group B1 (P＜0.01＝, and there was no statistical difference in it between two groups on the 8th day (P＞0.05). The incidence of SIRS in group A2 was significantly lower than that in group B2 (32.65% vs 52.63%, χ=5.328, P=0.021). In group A, the organ failure assessment score and the serum CRP were statistically lower than those in group B on the 4th day (P＜0.05）, and the hospital stay and the hospitalization costs were significantly lower than those in group B (P＜0.05＝. Multivariable logistic regression of patients without SIRS at admission showed that COX-2 inhibitor was a protective factor associated with the occurrence of SIRS (P＜0.05). Conclusion For patients with AP, COX-2 inhibitor pareoxib can reduce the incidence of SIRS, which is closely related to the improvement of SIRS and organ failure, but has no significant difference with the analgesic effect of opioids. It can reduce serum CRP and has good cost-effectiveness. COX-2 inhibitor parecoxib is an independent protective factor for the occurrence of SIRS.